A Multicentre and stratified study of the attitude of medical students towards organ donation in Spain. Issue 4 (19th May 2019) - Ríos, A.; López-Navas, A.; López-López, A.; Gómez, F.J.; Iriarte, J.; Herruzo, R.; Blanco, G.; Llorca, F.J.; Asunsolo, A.; Sánchez, P.; Gutiérrez, P.R.; Fernández, A.; et al.
ABSTRACT: Introduction: Medical students represent a new generation of medical thought, and if they have a favourable attitude towards organ donation this will greatly encourage its promotion. Objective: To analyse the attitude of medical students in Spanish universities towards the donation of their own organs and to determine the factors affecting this attitude. Material and Methods: Type of study: A sociological, interdisciplinary, multicentre, and observational study in Spain. Study population: Students studying a degree in medicine enrolled in Spain ( n  = 34, 000). Sample size: A sample of 9598 students (confidence of 99% and precision of ±1%), stratified by geographical area and academic year. Instrument of measurement: A validated questionnaire of attitude towards organ donation and transplantation (PCID-DTO RIOS) was self-administered and completed anonymously. Results: The questionnaire completion rate was 95.7% ( n  = 9.275). 80% were in favour of donation, 2% against and 18% were undecided. The following main variables were related to a favourable attitude: being of the female sex (Odds Ratio = 1.739); being in the sixth year of the degree (OR = 2.506); knowing a donor (OR = 1.346); having spoken about the subject with one's family (OR = 2.132) and friends (OR = 1.333); having a family circle that is in favour, more specifically, having a father (OR = 1.841), mother (OR = 2.538) or partner in favour (OR = 2.192); being a blood donor (OR = 2.824); acceptance of the mutilation of the body if it were necessary (OR = 2.958); and being an atheist or an agnostic (OR = 1.766). Conclusions: Spanish medical students generally have a favourable attitude towards organ donation, although 20% are not in favour.